Identification of Allergic Epitopes of Soybean β-Conglycinin in Different Animal Species - Zhao, Yuan; Naren, Gaowa; Qiang, Jianan; Qin, Guixin; Bao, Nan; Farouk, Mohammed Hamdy (Frontiers in Veterinary Science, 2021)
Soybean can cause allergy in both humans and animals. The herein study aims to identify the antigenic determinants (epitopes) of β-conglycinin that lead to allergy in different animal species (swine, bovine, and rats). The epitopes of β-conglycinin through Co-Immunoprecipitation and Mass spectrometry were identified. The binding abilities of seven identified epitope peptides to allergic sera of three animal species were compared by ELISA and dot-blot techniques. Some epitope peptides could be recognized by three animal allergic sera, while the most epitopes showed some differences in binding abilities to the different animal sera. The strongest reaction using swine sera was detected with peptide α2, β2 and β3, but the biggest sensitive region for the bovine and rats were the peptide α2, β1 and β4. Most epitopes of β-conglycinin exhibited different binding abilities to the three animal sera, in which the biggest sensitive regions were peptide α2, β2 and β3 for swine, but the peptide α2, β1 and β4 were detected for bovine and rats.